2014
DOI: 10.1016/j.anbehav.2014.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in chimpanzee reconciliation relate to social switching behaviour

Abstract: In recent years, the presence of stable individual variation in animal behaviour has been corroborated by studies across a wide variety of taxa and research disciplines. Reconciliation, or postconflict affiliation between former opponents, is a behavioural domain in which individual differences have not been systematically studied. Using a long-term data set comprising over 2000 conflict and postconflict observations in two groups of outdoor-housed chimpanzees, Pan troglodytes, we provide evidence for stable i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 45 publications
1
22
1
Order By: Relevance
“…Several of the behaviors in our categories of social behavior ( Figure 1) have already been shown to exhibit repeatable individual differences where some individuals exhibit more of the given social behavior than others regardless of circumstances or context. Proactivity has been shown to be repeatable over time (reviewed by Réale et al, 2007) and there are consistent individual differences in parental behavior (Budaev, Zworykin, & Mochek, 1999;Fairbanks, 1996;Maestripieri, 1993;Schwagmeyer & Mock, 2003), affiliative behavior (Seyfarth, Silk, & Cheney, 2012;Webb, Franks, Romero, Higgins, & de Waal, 2014), and alloparental behavior in cooperative breeders (Carter, English, & Clutton-Brock, 2014;English, Nakagawa, & Clutton-Brock, 2010). Furthermore, individual differences in measures of HPA-axis activity exist (Baugh, van Oers, Dingemanse, & Hau, 2014;Ellis, Jackson, & Boyce, 2006;Fletcher, Dantzer, & Boonstra, 2015) and has been observed to co-vary with different behavioral types (Carere et al, 2010;Cockrem, 2007;Koolhaas et al, 1999;Korte, Koolhaas, Wingfield, & McEwen, 2005).…”
Section: Iver S It Y Of So Cial B Ehavi Ormentioning
confidence: 99%
“…Several of the behaviors in our categories of social behavior ( Figure 1) have already been shown to exhibit repeatable individual differences where some individuals exhibit more of the given social behavior than others regardless of circumstances or context. Proactivity has been shown to be repeatable over time (reviewed by Réale et al, 2007) and there are consistent individual differences in parental behavior (Budaev, Zworykin, & Mochek, 1999;Fairbanks, 1996;Maestripieri, 1993;Schwagmeyer & Mock, 2003), affiliative behavior (Seyfarth, Silk, & Cheney, 2012;Webb, Franks, Romero, Higgins, & de Waal, 2014), and alloparental behavior in cooperative breeders (Carter, English, & Clutton-Brock, 2014;English, Nakagawa, & Clutton-Brock, 2010). Furthermore, individual differences in measures of HPA-axis activity exist (Baugh, van Oers, Dingemanse, & Hau, 2014;Ellis, Jackson, & Boyce, 2006;Fletcher, Dantzer, & Boonstra, 2015) and has been observed to co-vary with different behavioral types (Carere et al, 2010;Cockrem, 2007;Koolhaas et al, 1999;Korte, Koolhaas, Wingfield, & McEwen, 2005).…”
Section: Iver S It Y Of So Cial B Ehavi Ormentioning
confidence: 99%
“…Interestingly, the motivation to actively manage one’s environment has recently been posited as an important individual difference among chimpanzees. Analyses revealed that those animals who engage in the most task-switching—those animals who make the most active changes in managing the environment—are also the same individuals who engage in the most reconciliatory behavior following conflicts, a behavior that involves a great deal of monitoring and control ( Webb et al, 2014 ). Thus the “how” motivation (control) is not only an integral and basic part of approach/avoidance goal pursuit, it is an independent motivation deserving of study in its own right.…”
Section: Truth and Control Motives: The “What” And “How” Of Approach mentioning
confidence: 99%
“…That some subjects in our study rarely reconciled, while others did so rather frequently, is an area that also warrants further study. Individual variation may reflect the variable quality of the relationships of different individuals (with higher reconcilers having more valuable bonds) or stable individual differences, as recently emphasized by work incorporating conflict management skills as a component of broader animal personality (Webb, Franks, Romero, Higgins, & de Waal, 2014;Webb, Romero, Franks, & de Waal, 2017;Webb & Verbeek, 2016).…”
Section: Discussionmentioning
confidence: 99%